Froggy learns to swim - London, Jonathan, 1947-; Remkiewicz, Frank (New York : Viking, 1995)
Froggy is afraid of the water until his mother, along with his flippers, snorkle, and mask, help him learn to swim.
Keywords: Swimming -- Fiction; Fear -- Fiction; Frogs -- Fiction; Mothers and sons -- Fiction